PENCATATAN AKUNTANSI PADA USAHA MIKRO,KECIL, DAN MENENGAH ( UMKM) TERHADAP IMPLEMENTASI STANDAR AKUNTANSI ENTITAS TANPA AKUNTABILITAS PUBLIK (SAK-ETAP) - Andrianto, Andrianto (Majalah Ekonomi, 2016)
Abstract This study describes the accounting records at the Sector Micro, Small and Medium Enterprises (SMEs) in PD. Prohibition -Sidoarjo market in the implementation of the Accounting Standards Entities Without Public Accountability (SAK -ETAP) issued in 2009. From the results of Research has shown that most of the traders SME sector in PD. Prohibition -Sidoarjo market still perform minimally accounting records and accounting reporting only be done only on the management of businesses that do not run themselves. Besides, it is also due to limited educational background of the SMEs in PD. Surya market Larangan- Sidoarjo.